Transcranial Current Stimulation as a Tool of Neuromodulation of Cognitive Functions in Parkinson’s Disease - Brak, Ivan V.; Filimonova, Elena; Zakhariya, Oleg; Khasanov, Rustam; Stepanyan, Ivan (Frontiers in Neuroscience, 2022)
Decrease in cognitive function is one of the most common causes of poor life quality and early disability in patients with Parkinson's disease (PD) (Aarsland et al., 2017). Existing methods of treatment are aimed at both correction of motor and non-motor symptoms. Methods of adjuvant therapy (or complementary therapy) for maintaining cognitive functions in patients with PD are of interest. A promising subject of research in this regard is the method of transcranial electric current stimulation (tES). Here we reviewed the current understanding of the pathogenesis of cognitive impairment in PD and of the effects of tDCS and tACS on the cognitive function of patients with PD-MCI (Parkinson's Disease–Mild Cognitive Impairment).